The Dynamics of the Development of Walking Tourism Among the Adult Population of the Southern Region of Ukraine in the Second Half of the XXth and the Beginning of the XXIst Century - Oleksandr Kilnytskyi (Lesya Ukrainka Volyn National University, 2018)
Sports tourism as a kind of sport is developing in all former Soviet Union countries. The first steps to establish sports tourism were made in Tsarist Russia, and the rapid development was reached during the period of Soviet Union. There were ups and down in development of the sports tourism in Ukraine. The basis for the development of any sport are indicators of the involvement of children and youth. That's why the basis of the study is the study and analysis of the development of walking tourism among adults in Kherson, Mykolaiv and Odessa regions. According to the study, there were a number of phases in the sports tourism development: hiking was the main form of sports tourism, which was developing during the time of the former Soviet Union. The sports tourism in Southern regions of Ukraine depends on several factors, which have both positive and negative impacts on the development.